Implementation of Deep Systems Approach Learning - Amiruddin Amiruddin; Aidatul Fauziah; Nabilah Ulfiah Nasution; Nindi Aulia Putri; Martyr Aulia Fahra Harahap (Edumaspul: Jurnal Pendidikan, 2022)
A system is a set of components or elements that interact with each other to achieve a goal. The learning principle is a guide for teachers in implementing effective learning conditions. There are two characteristics of the teaching systems approach, namely the systems approach and the teaching and learning process to make it easier for students to learn. The method that can be used to determine the quality of the educational process is a systems approach. Through a systems approach, you can see all aspects of the impact of a successful process. Learning is called having a system because it contains components that are interrelated and influence one another. Teachers, students, learning materials, methods, media, facilities and infrastructure are the components included in the study. The availability and effectiveness of each of these components will determine the success or failure of a lesson.